Sistem Bagi Hasil Perkebunan Kelapa Sawit Terhadap Kesejahteraan Masyarakat Dalam Perspektif Ekonomi Islam Di Desa Sekutur Jaya Kecamatan Serai Serumpun Kabupaten Tebo - M. Bagus Permana; A.A Miftah; Muhammad Subhan (Sekolah Tinggi Ilmu Administrasi Yappi Makassar Jl. Sumba no 46, Kota Makassar, Sulawesi Selatan, 2024)
One of the systems for cultivating oil palm plantations used by residents in Allied Jaya is the profit sharing system (musaqah). For farmers who do not have garden land, they work to manage the gardens of other farmers who have land. All costs in terms of cultivating the land are borne by the land owner. Apart from that, the custom of the people of Aller Jaya Village in carrying out cooperation in sharing plantation products is not to set a time limit, not to write down a written agreement, and there are no witnesses in its implementation. The provisions in muamalah fiqh state that every time an agreement is made, a time limit must be set and it should be written down to avoid disputes between the two parties. However, this cannot be separated from the knowledge and understanding of the people of Aller Jaya Village. The aim of this research is to find out how the oil palm plantation profit sharing system affects the welfare of the community in the village of Allyr Jaya from an Islamic economic perspective. Checking the validity of the data using Triangulation techniques and data collection methods using observation, interviews and documentation. The informants for this research are land owners and land cultivators. Based on the results of this research, it shows that the existence of this profit sharing cooperation has an impact on the welfare of the community in terms of material needs, increasing income so that daily needs are met. However, not only material needs can be met, spiritual needs can also be met. However, the oil palm plantation profit sharing system in Allyr Jaya Village is not fully in accordance with Islamic economics in the musaqah agreement.